RNA-seq profile of African American men with a clinically localized prostate cancer - Naoya Nagaya; Jeffrey Rosenfeld; Geun Taek Lee; Isaac Yi Kim (Prostate International, 2021)
Background: Prostate cancer in African American (AA) men has a poor prognosis. This study aimed to identify potential genetic risk factors for prostate cancer in AA men. Methods: We used prostate cancer tissue from 61 patients who underwent radical prostatectomy. We compared somatic gene expression in Caucasian (CA) and AA men using RNA sequencing. Results: By comparing the RNA-seq data obtained from prostate cancer tissue between AA and CA men, this study showed a significant difference in expression levels of 45 genes. Pathway analysis of 45 genes using Kyoto Encyclopedia of Genes and Genomesenrichment analysis revealed a neuroactive ligand–receptor interaction signal. In addition, the results of the Ingenuity Pathway Analysis showed pathways involved sphingosine-1-phosphate signaling. Furthermore, validating 45 genes in the The Cancer Genome Atlas (TCGA) Provisional cohort, cholinergic receptor muscarinic 3 expression level was significantly lower in AA than in CA men, and the results showed a significantly higher rate of biochemical recurrence in patients with low expression. Conclusions: We identified genetic differences of clinically localized prostate cancer in AAs and CAs by RNA sequencing.